A framework for building climate storylines based on downward counterfactuals: The case of the European Union Solidarity fund - Alessio Ciullo; Olivia Martius; Eric Strobl; David N. Bresch (Climate Risk Management, 2021)
Recent research introduced the concept of climate storylines as an alternative approach to estimate climate impact and better deal with uncertainties. A climate storyline is an event-based approach which aims at building “physically self-consistent unfolding of past events, or of plausible future events or pathways”. As such, climate storylines may profit from downward counterfactual thinking, which aims at analyzing how past events could have been worse. Notwithstanding the various applications of downward counterfactual thinking in the natural risk management literature, no study relates this with the climate storyline approach. The main goal of this paper is thus to introduce a framework that supports the development of climate storylines from downward counterfactuals. The framework is event-oriented, it focuses on impact, and it is designed to be applied in a participatory fashion. As a proof-of-concept application, we study the impact of tropical cyclone events on the European Union Solidarity Fund (EUSF) and do not conduct a participatory analysis. These events represent a serious threat to the European outermost regions, and their impact to the EUSF capital availability has never been studied. We find that payouts due to tropical cyclones can hamper a recovery of the fund if large payouts concurrently occur in mainland Europe. To avoid this also considering future changes, an increase in capitalization up to 90 % percent may be required.